1976
DOI: 10.2337/diab.25.4.256
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Nucleotides in Pancreatic Islets: Tolbutamide- and Arginine-induced Insulin Release

Abstract: With the use of isolated rat islet perfusion, levels of the islet cyclic adenosine 3' ,5' -monophosphate (cAMP) were compared with dynamic insulin secretion induced by tolbutamide and arginine. Tolbutamide elevated islet cAMP rapidly and augmented both glucose-induced islet cAMP levels and insulin secretion; arginine, however, did not elevate islet cAMP but did enhance glucose-induced insulin secretion. Since the latter result could have been modulated by cyclic guanosine 3' ,5' -monophosphate, this cyclic nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

1979
1979
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 5 publications
2
16
0
Order By: Relevance
“…These effects may be due to elevation of intracellular Ca 2ϩ , which leads to activation of adenylcyclase. Our results are in agreement with data showing that glucose, in addition to other agents, stimulates insulin secretion through cAMP-dependent mechanisms (20).…”
Section: Fig 5 Effect Of High Glucose (A)supporting
confidence: 93%
See 1 more Smart Citation
“…These effects may be due to elevation of intracellular Ca 2ϩ , which leads to activation of adenylcyclase. Our results are in agreement with data showing that glucose, in addition to other agents, stimulates insulin secretion through cAMP-dependent mechanisms (20).…”
Section: Fig 5 Effect Of High Glucose (A)supporting
confidence: 93%
“…There is evidence in the literature that GLY affects respiration and ATP content in rat islets (16 -19). Through use of islet homogenates, tolbutamide (another SU) and its analogs have been shown to inhibit islet phosphodiesterase (20) and increase c-AMP levels. SUs also modulate the sodium content in rat pancreatic islets (21,22).…”
mentioning
confidence: 99%
“…cAMP concentration as earlier studies have shown that TLB and GLB can rapidly raise levels of cAMP in islets. 14,15 However, Zhang et al…”
Section: Resultsmentioning
confidence: 99%
“…The suggestion that cyclic-AMP is involved in the stimulation of insulin release by sulphonylureas is based on the evidence that these drugs transiently increase cyclic-AMP levels in islet cells [36,37] by stimulating adenylate cyclase [16] or inhibiting phosphodiesterase [38,39], two observations made in homogenates of islet cells. In the present experiments, inhibition of the phosphodiesterase by theophylline was able to increase the rate of insulin release when the stimulating effect of tolbutamide had declined.…”
Section: Discussionmentioning
confidence: 99%